1998
DOI: 10.1101/gad.12.14.2164
|View full text |Cite
|
Sign up to set email alerts
|

Impaired megakaryopoiesis and behavioral defects inmafG-null mutant mice

Abstract: The small Maf proteins (MafG, MafK, and MafF), which serve as heterodimeric partner molecules of CNC family proteins for binding in vitro to MARE sites, have been implicated in the regulation of both transcription and chromatin structure, but there is no current evidence that the proteins fulfill these functions in vivo. To elucidate possible contributions of the small Maf proteins to gene regulation, we have ablated the mafG and mafK genes in mice by replacing their entire coding sequences with the Escherichi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
127
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 102 publications
(135 citation statements)
references
References 34 publications
8
127
0
Order By: Relevance
“…We previously isolated phage clones containing the mouse mafG locus and mapped coding exons II and III but did not determine the nature of the noncoding first exon(s) (13). Therefore, we first performed 5Ј-RACE to determine first exon(s) utilized by the mafG gene and identified three (designated Ia, Ib, and Ic) ( Fig.…”
Section: Nrf2 Activates Mafg Through An Are 4485mentioning
confidence: 99%
See 1 more Smart Citation
“…We previously isolated phage clones containing the mouse mafG locus and mapped coding exons II and III but did not determine the nature of the noncoding first exon(s) (13). Therefore, we first performed 5Ј-RACE to determine first exon(s) utilized by the mafG gene and identified three (designated Ia, Ib, and Ic) ( Fig.…”
Section: Nrf2 Activates Mafg Through An Are 4485mentioning
confidence: 99%
“…The functions of small Maf proteins are compensatory and provide partially overlapping redundancy, since small maf single mutant mice (mafG Ϫ/Ϫ , mafK Ϫ/Ϫ , and mafF Ϫ/Ϫ ) showed mild or subtle phenotypes (12)(13)(14), whereas small maf compound mutant mice (mafG Ϫ/Ϫ :mafF Ϫ/Ϫ and mafG Ϫ/Ϫ :mafF Ϫ/Ϫ :mafK Ϫ/Ϫ ) displayed a greater number of and more profound deficiencies (15, 16).…”
mentioning
confidence: 99%
“…Genetic and biochemical studies have revealed that the small Maf-p45 heterodimer, which is also known as NF-E2, serves as an indispensable transcriptional activator for terminal megakaryocyte differentiation (17,24,29,31). The megakaryocytes of p45-null mutant mice proliferate and differentiate in response to thrombopoietin, without practically any proplatelet generation.…”
mentioning
confidence: 99%
“…[1][2][3][4] It is composed of two subunits (p45 and p18), each of which contains a basic region-leucine zipper DNA binding domain. 3,5 The p18 subunit is a small Maf protein, [6][7][8] namely MafG, which partners the p45 subunit (ie p45 NF-E2) in megakaryocyte (MK) development. 8 The heterodimers of p45 and small Mafs can activate transcription via Mares (ie Maf recognition elements: TGCTGAC(T/GT)CAGCA), whereas the homodimers of small Mafs form repressors that act on the same sites.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 The p18 subunit is a small Maf protein, [6][7][8] namely MafG, which partners the p45 subunit (ie p45 NF-E2) in megakaryocyte (MK) development. 8 The heterodimers of p45 and small Mafs can activate transcription via Mares (ie Maf recognition elements: TGCTGAC(T/GT)CAGCA), whereas the homodimers of small Mafs form repressors that act on the same sites. 6,9 Acetilation by cAMP-response element-binding protein (CREB)-binding protein (CBP) augments DNA binding of p45 NF-E2.…”
Section: Introductionmentioning
confidence: 99%